Implications of Family Cohesion and Conflict for Adolescent Mood and Well‐Being: Examining Within‐ and Between‐Family Processes on a Daily Timescale. Issue 4 (4th December 2019) - Fosco, Gregory M.; Lydon‐Staley, David M.
Abstract : Family‐level conflict and cohesion are well‐established predictors of adolescent mental health. However, traditional approaches focusing on between‐family differences in cohesion and conflict may overlook daily intrafamily variability that might provide important new information. We used data from a 21‐day daily diary protocol in a sample of 151 caregivers (95.3% female) and their adolescent child (61.5% female) in two‐caregiver families to test whether daily changes in family functioning are associated with daily changes in adolescent well‐being and whether adolescent well‐being depends on average levels of family functioning. We examined family cohesion and conflict in relation to adolescent angry, depressed, and anxious mood, as well as happiness, life satisfaction, and meaning and purpose in life in multilevel models. Both cohesion and conflict exhibited meaningful daily variation. Adolescent‐reported cohesion and conflict had unique within‐family associations with all six adolescent outcomes. Models using parent reports of family functioning yielded fewer associations than models with adolescent reports; however, several findings remained. Cross‐level interactions indicated that within‐family variations in cohesion were only associated with adolescent depression in families with lower average levels of cohesion across days. In sum, this study provides compelling evidence that families exhibit meaningful variability from day to day and that daily variation has important implications for adolescent well‐being. Abstract : El conflicto y la cohesión a nivel familiar son predictores bien establecidos de la salud mental adolescente. Sin embargo, los enfoques tradicionales que se centran en diferencias interfamiliares en la cohesión y el conflicto pueden pasar por alto la variabilidad intrafamiliar diaria que podría proporcionar información importante y nueva. Utilizamos datos de un protocolo de registro diario de 21 días en una muestra de 151 cuidadores (el 95.3 % de sexo femenino) y su hijo adolescente (el 61.5% de sexo femenino) en familias de dos cuidadores para evaluar si los cambios diarios en el funcionamiento familiar están asociados con los cambios diarios en el bienestar de los adolescentes, y si el bienestar de los adolescentes depende de los niveles promedio de funcionamiento familiar. Analizamos la cohesión y el conflicto familiar en relación con los estados de ánimo de enojo, depresión y ansiedad así como de felicidad, satisfacción con la vida, y significado y propósito en la vida en modelos multinivel. Tanto la cohesión como el conflicto demostraron una variación diaria significativa. La cohesión y el conflicto informados por los adolescentes tuvieron asociaciones únicas dentro de las familias con los seis resultados de los adolescentes. Los modelos que utilizaron informes de los padres del funcionamiento familiar indicaron menos asociaciones que los modelos con informes de los adolescentes, sin embargo, quedaron varios hallazgos. Las interacciones a nivel transversal indicaron que las variaciones en la cohesión intrafamiliar estuvieron solamente asociadas con la depresión de los adolescentes en las familias con niveles promedio más bajos de cohesión a lo largo de los días. En resumen, este estudio ofrece pruebas convincentes de que las familias demuestran una variabilidad significativa día a día y de que la variación diaria tiene importantes implicancias para el bienestar de los adolescentes. Abstract : 家庭层面的冲突和家庭的凝聚力是公认的衡量青少年心理健康的指标。但是，传统研究方法侧重于家庭和家庭之间在凝聚力和冲突方面的差异，通常会忽略某个具体家庭内部的日常变异性，而后者可能会提供重要的新信息。本研究的参与者来自家中有两个照料者的家庭的照顾者共151名（女性占95.3％），以及他们的青春期孩子（女性占61.5％），我们使用的数据来自他们持续21天的每日记录中的数据，用以测试家庭功能的每日变化是否与青少年的幸福感的每日变化相关，以及青少年的幸福感是否取决于家庭功能的平均水平。我们采用多层次模型来研究家庭凝聚力和家庭冲突，他们与青少年生气，沮丧和焦虑情绪以及快乐，生活满意度以及生活中的意义和目的之间的相互关联。研究得出在凝聚力和冲突方面，每天都表现出有意义的变化。青少年报告的凝聚力和冲突与六个青春期结果之间有特殊的家庭内部的关联。使用父母方面报告的家庭功能数据的模型所产生的关联要少于使用青少年方面报告的数据的模型。本研究还有几个发现。跨层次的交互作用表明，家庭内的凝聚力差异仅与生活在家庭内聚力平均水平以下的家庭的青少年抑郁有关。总而言之，这项研究提供了令人信服的证据，表明家庭生活每天都会表现出有意义的差异性，而且每日的差异都会对青少年的幸福感具有重要的影响。